The influence of cultural orientation on the entrepreneurial motivation of Chinese female returnee entrepreneurs—From the perspective of cultural integration - Zhang, Yaqiong (Frontiers in Communication, 2023)
Based on the self-construction theory, this paper is devoted to the analysis of the influence of cultural orientation, cultural integration on female returnee entrepreneurs' entrepreneurial motivation, and conducted the following investigations:(A) The current cultural orientation of Chinese female returnee entrepreneurs (masculinity/femininity);(B) The current entrepreneurial motivation of Chinese female returnee entrepreneurs (necessity/opportunity);(C) The influence of cultural orientation on entrepreneurial motivation;(D) Whether cultural integration has a moderating role in the C relational process.A total of 488 Chinese female returnee entrepreneurs participated in the survey. The structural equation modeling (SEM) and multi-group analysis were used to evaluate the relationship between the model structures. It provides a new perspective on the relationship between female returnee entrepreneurs' cultural orientation, entrepreneurial motivation, and the role of cultural integration.The results show that due to the influence of globalization and diversified cultural background, the cultural orientation of Chinese female returnee entrepreneurs tends to be more feminine rather than traditional masculine, and they pay more attention to meeting the entrepreneurial motivation of opportunity, such as interests, self-value expression and market opportunities, rather than simple survival. Cultural orientation has a significant influence on the entrepreneurial motivation of Chinese female entrepreneurs, and cultural integration plays a moderating role in this influence. The last part of the paper summarizes the theoretical and practical significance.